Characterization of mānuka and rosemary oils as antimicrobial and antioxidant agents for meat applications : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology at Massey University, Palmerston North, New Zealand - Kaur, Ramandeep (Massey University, 2023)
The usage of chemical preservatives in meat products has been associated with adverse health effects, which is driving consumers' preferences towards natural preservatives. Raw and processed meats have been linked to cancers due to the presence of nitrate/nitrite as a chemical preservative. In recent years, extensive innovative and promising approaches have been exploited to entirely or partially replace synthetic preservatives. Plant-based natural preservatives possessing antioxidant and antimicrobial characteristics can be ideal for food applications. Essential oils are aromatic liquids extracted from different plant parts, such as leaves, bark, roots, and seeds, and are rich sources of bioactive compounds like monoterpenes, sesquiterpenes, and oxygenated sesquiterpenes and phenolic compounds. As per the literature, essential oils possessing antioxidant and antimicrobial characteristics have been reported to decline the rate of oxidative reactions and microbial growth. This study aims to harness the potential of essential oil obtained from the indigenous plant of New Zealand, i.e., mānuka, as a natural antioxidant and antimicrobial agent for meat preservation than chemical preservatives like nitrates/nitrites. As per the available literature, β-triketones are responsible for the antimicrobial characteristics of mānuka oil. We hypothesise that using antioxidants and antimicrobial bioactive compounds of Leptospermum scoparium (mānuka) will improve the shelf life and stability of the meat products. The first research objective characterised and compared the antioxidant and antimicrobial potential of mānuka oil with different triketone contents (5, 25, and 40 %) and kānuka oil with a commonly used natural preservative, i.e., rosemary oil. In chemical composition, kānuka oil possessed higher levels of α-pinene, while rosemary oil exhibited higher amounts of 1,8 cineole and α-pinene as primary compounds. In mānuka oils, the concentration of other compounds decreased as triketone content increased from 5 to 40 %. A comparison of the antioxidant characteristics of these oils was also made with chemical antioxidants, i.e., butylated hydroxytoluene (BHT). It was observed that mānuka oils possess higher antioxidant properties than rosemary and BHT (at both the lowest tested concentrations of 0.1 % and 1 %). In the antimicrobial efficacies assay results, all mānuka oils showed more effectiveness against Listeria monocytogenes and Staphylococcus aureus than Salmonella and Escherichia coli. However, the inhibition effect of rosemary oil was greater against Salmonella and Escherichia coli than mānuka oil (Chapter 3). The minimum inhibitory concentration of all mānuka oils required to inhibit Listeria monocytogenes and Staphylococcus aureus was below 0.04 %, while kānuka and rosemary oil inhibited these microbes at 0.63 and 2.5 %, respectively. On the other hand, a minimum 2.5 % concentration of all oils was needed to inhibit Salmonella and Escherichia coli. These results indicated that mānuka oil can be used as an antimicrobial agent, particularly against tested Gram-positive microbes (at a very concentration of 0.04 %) in meat products, while rosemary oil can be used against all tested microbes at 2.5 %. However, meat constituents such as fats have a significant effect on the efficacies of added bioactive compounds, therefore, it is essential to have insights into the lipophilicity of added essential oils and their bioactive compounds. In the next research experiment, to confirm the lipophilic behaviour of chemical compounds present in mānuka oil, the octanol-water partition coefficient of beta-triketones (leptospermone, isoleptospermone, and flavesone), α-pinene and γ-terpinene were elucidated using shake flask method (Gas chromatography and mass spectrometry) and predicted using EPI software (Chapter 4). High values of the octanol-water partition coefficient of these compounds indicate their more affinity towards the fat than the water. Further, when the concentration of the compounds separated in 3 and 12 % beef-fat and water systems was determined, all compounds showed higher concentrations in water of the low-fat system than in the high-fat. The findings pointed out that essential oils may exert an antioxidant effect in the high-fat system to prevent lipid oxidation; however, their antimicrobial effect may be reduced due to the presence of fat, and higher concentrations of these oils may be needed to achieve an antimicrobial effect against selected microbes. In the third research experiment, selected mānuka and rosemary oils were used as natural antioxidants and antimicrobial agents in low and high-fat meat pastes prepared from commercial-breed and wagyu beef tenderloins, respectively (Chapter 5). These effects were compared against the chemical preservative sodium nitrate and butylated hydroxytoluene during refrigerated storage of meat pastes at 4 °C. In commercial and wagyu beef pastes, a lower number of Listeria monocytogenes and Staphylococcus aureus were observed in mānuka and rosemary oil treatments than in the sodium nitrate and control samples (without added preservative). Rosemary oil also delayed the growth of Salmonella and Escherichia coli more than mānuka oil added and control samples. In terms of oxidative stability, mānuka oil added wagyu beef pastes were more stable and showed the lowest lipid oxidation values than all treatments. In commercial beef samples, no significant difference between essential oils added samples, either mānuka or rosemary oil and control samples was observed. There was a significant change in pH values of all wagyu and commercial beef samples, whilst these changes were greater in untreated samples (controls) than in the essential oils-treated samples. Despite the promising antioxidant and antimicrobial characteristics of essential oils, these are rarely utilised in food products owing to their easy degradation, low water solubility, low stability, and unwanted odour and flavour. The application of essential oils in encapsulated form is an effective and innovative approach to overcome these limitations by covering the core materials (oil droplets) in carrier materials. In addition, it improves stability and provides controlled release and targeted delivery of essential oils in foods. In the next research objective, mānuka and rosemary oils-containing nonentities (nanoemulsions and nanocapsules) made of sodium alginate and whey protein were fabricated and compared for their thermal stability and release characteristics (Chapter 6). The particle size and zeta potential of prepared nanoentities were between 100 -600 nm and -10 to -40 mV, confirming that the obtained nanoemulsions and nanocapsules were stable and in the nano range. The obtained nanoentities were observed to be more thermostable, sustained release profile than the free form of oils while showing a lower in vitro antioxidant effect. The release mechanism of the essential oil from nanoemulsions and nanocapsules was also studied using different mathematical models. The release mechanism of essential oil from nanoemulsions and nanocapsules followed Higuchi’s law, which indicates that the solvent first penetrates the encapsulated matrix and then dissolves the embedded oil droplets through the diffusion process. The delayed or sustained release from encapsulated oil might influence the antioxidant and antimicrobial activity of essential oils in meat pastes. However, a food matrix made up of different constituents can affect the partitioning and release of essential oils from the carrier material, and consequently, their preservative effect may vary according to the meat paste. An improvement in the antioxidant activity of oils after emulsification was observed as nanoemulsions of both oils had the lowest TABRS values in crossbred and wagyu pastes (Chapter 7). Mānuka oil and its nanoentities had more antioxidant effects than rosemary oil. In wagyu pastes, there was a significant difference in nanoemulsions added pastes than the other treatments, while in crossbred pastes, no significant differences were noted between free oils and nanoentities containing beef pastes. Despite the antioxidant efficacies, the antimicrobial activity of free, nanoemuslfisied and nanoencapsulated oils was also determined in the wagyu and crossbred beef pastes during refrigerated storage (4 °C) of two weeks. These antimicrobial effects were compared against controls (without added preservatives) and sodium nitrite-added paste samples. There was a significant increase in microbial counts of all inoculated-paste samples, whilst this increase was lower in preservatives added samples than in the controls. In wagyu and crossbred beef pastes, mānuka oil and its nanoentities delayed the growth of Listeria monocytogenes and Staphylococcus aureus, and mānuka-nanoemulsions exhibited the lowest number of these microbes than all other treatments. However, rosemary oil and its nanoforms effectively inhibited Salmonella and Escherichia coli during refrigerated storage at 4 °C. To better understand the mechanism for the antimicrobial activity of essential oils against selected pathogens, cell viability membrane integrity and the release of intracellular compounds and proteins through fluorescence-based assays were determined. In all these assay results, mānuka and rosemary oils treatment of Listeria monocytogenes, Staphylococcus aureus, Salmonella and Escherichia coli exhibited a decline in cell viability, disrupted cell-wall permeability and enhanced release of intracellular compounds and proteins from cells than the untreated cells. Scanning electron micrographs also confirmed that these mechanisms were responsible for the antibacterial efficacy of mānuka and rosemary oil. To correlate the effect of fat content on varied antimicrobial characteristics of essential oils in meat pastes, the partitioning of essential oils in different phases, such as octanol, beef and water, was determined. Overall, the work showed that mānuka oil has the potential to be used in meat pastes as an antimicrobial agent, especially against tested Gram-positive (Listeria monocytogenes and Staphylococcus aureus). In addition, this oil can be used to completely replace synthetic antioxidants like butylated hydroxytoluene to inhibit lipid oxidation in high-fat meat systems. Due to the lipophilic nature of oils, the fat content of meat systems significantly affects the partitioning of these oils in water and fat phases, which in turn affect their antimicrobial efficacies.
Figures 2.1, 2.3 A, 2.4 & 2.5 are reproduced with permission. Figures 2.2 & 2.3 B are reproduced under a CC BY 4.0 DEED license.
Keywords: Meat; Microbiology; Leptospermum scoparium; Food preservatives; Essences and essential oils; 300607 Food technology